Fame and fandom : functioning on and offline - Lam, Celia; Raphael, Jackie; Middlemost, Renee, 1980-; Balanzategui, Jessica (Fandom & culture., 2022)
"Celebrities depend upon fans to sustain their popularity and livelihood, and fans are happy to oblige. With social media, they can follow their favorite (or least favorite) celebrities' every move, and get glimpses into their lives, homes, and behind-the-scenes work. Fans interact with celebrities now more than ever, and often feel that they have a claim on their time, attention, and accountability. In Fame and Fandom: Functioning On and Offline, contributors examine this tumultuous dynamic, and bring together celebrity studies and fan studies like never before. This volume explores the intersections between fan cultures, communities and practices around the globe; as well as the formation and maintenance of celebrity and public personas. It expands knowledge of the fields by examining both online and offline examples. Readers will find new theoretical approaches to fan/celebrity encounters, as well as discussion of parasocial relationships and fan interactions with celebrities. Case studies include Supernatural, Harry Styles, YouTube influencers, film location sites, Keanu Reeves, and celebrities as fans. This volume is ideal for anyone curious about the mutual influences of fame on fandom, and vice versa"--